Многопараметрические гибридные схемы изолированного разделения каналов в интегральных сотовых сетях связи. І - Меликов, А.З.; Пономаренко, Л.А.; Велиджанова, Г.М. (Управляющие системы и машины, 2016)
Предложена многопараметрическая схема изолированного разделения общего пула каналов в интегральной сотовой сети связи, в которой обрабатываются новые и хэндовер-вызовы данных и речи. Выделены две индивидуальные зоны каналов для вызовов данных и речи и общая зона для их совместного использования. Рассмотрены два варианта доступа разнотипных вызовов в общую зону. Приведены результаты численных экспериментов. Запропоновано багатопараметричну схему ізольованого розподілу загального пулу каналів в інтегральній стільниковій мережі зв’язку, де обробляються нові та хендовер-виклики даних і мови. Виділено дві індивідуальні зони каналів для викликів даних і мови та загальна зона для їх спільного використання. Розглянуто два варіанти доступу різнотипних викликів до загальної зони. Подано результати числових експериментів. Introduction. In Integrated Cellular Network (ICN) four type of calls are distinguished: handover voice calls (hv-calls), new voice calls (ov-calls), handover data calls (hd-calls) and new data calls (od-calls). The indicated calls have the different quality of service (QoS) requirements. To satisfy these requirements of heterogeneous calls in the available literature several channels partition schemas are proposed. Purpose. New two schemas to partition of common channels in Integrated Cellular Network (ICN) are proposed. The indicated schemas allow to satisfy the different requirement of heterogeneous calls to quality service (QoS) metrics. Both schemas are based on the idea of Isolated Partition with Common Zone (IPwCZ). In both schemas in individual zone the guard channels scheme for handover calls is used. In one of them (IPwCZv1) the common zone of channels is used by Complete Sharing (CS) scheme; in another scheme (IPwCZv2) in common zone of channels the cutoff scheme is used. The effective methods to calculate the QoS metrics of heterogeneous calls is developed. Method. The functioning of the investigated model is described by two-dimensional Markov Chain (2-D MC). Infinitesimal matrix of appropriate 2-D MC in both schemas are developed. It is shown that stationary distribution of indicated 2-D MC in both cases have multiplicative form and explicit formulas are developed. The algorithms to calculate QoS metrics of the different types of calls are proposed. Results. The results of numerical experiments for both schemas of channels partitions are demonstrated. In order to be concrete only dependencies of QoS metrics on parameters of channels partition schemas are shown. These results allow to perform detailed analysis of QoS metrics behavior in wide area of the different models. Conclusion. Simple algorithms to calculate QoS metrics in ICN are developed. Complexities of the algorithms are very low and they allow to select the optimal partition scheme in the investigated networks. The last problems will be studied in the future works.